Analisis Kebutuhan Pembelajaran Pendidikan Agama Islam di SDLB Yayasan Amal Mulia Indonesia - Setiady, Dicky; Khiyaroh, Nada Laili; A’yun, Sania Qurrota (Permata : Jurnal Pendidikan Agama Islam, 2023)
The research aims to uncover and analyze the needs required to implement Islamic Education (PAI) learning in the Special School for Disabilities (SDLB) of Yayasan Amal Mulia Indonesia. The analysis is conducted through describing the factors that hinder and support the learning process. This research adopts a qualitative method, specifically ethnographic research, by interviewing PAI teachers in the SDLB of Yayasan Amal Mulia Indonesia and the Head of the SDLB, as well as conducting school observations. The research findings indicate that inhibiting factors include media facilities, cooperation with the government, the quantity of teachers, and issues regarding teaching resources for Quranic reading among hearing-impaired students. Supportive factors include the teachers' enthusiasm for teaching and cooperation with parents. In terms of needs analysis, it is necessary to establish an Islamic education curriculum specifically designed for children with special needs. Cooperation between the government and the school appears to be an urgent matter for addressing the aspirations and communication needs of the school. Additionally, raising awareness among the government regarding the implementation of PAI learning in the SDLB of Yayasan Amal Mulia Indonesia seems to be a requirement for the successful execution of the PAI curriculum.Keyword: Needs Analysis; Learning Needs; Islamic Education Learning.